Prevalence of urinary incontinence and its relation to occupational status among Egyptian female patients presenting with chronic cough - Ragy Mamdouh Ghaly; Alaa Mohamed Atef Karim Eldin; Dina Abbas Mohamed AbdelRahman; Marwa Hussein Elassal (The Egyptian Journal of Bronchology)
Abstract Background Coughing is frequently linked to urinary incontinence (UI) in women. However, there is few information about its actual prevalence among women with chronic cough. There are some previous studies that link urinary incontinence to the occupational status. Aim of work To measure the prevalence of stress urinary incontinence and to identify the relationship between urinary incontinence and occupational status among female patients with chronic cough. Materials and methods A cross-sectional study was conducted on 80 female patients presented with chronic cough of any cause, and all patients were interviewed using a structured questionnaire that included personal, occupational, chronic cough, and urinary incontinence questionnaire. General and local examination were done. Results Out of 80 patients, 55% were found to have stress urinary incontinence. Gastroesophageal reflux disease (GERD) was the most prevalent cause of chronic cough (48.8%) followed by bronchial asthma (22.5%). Most of the studied patients (90.9%) reported that leaking of urine interferes with their quality of life. The frequency of UI among working females was significantly higher than nonworkers. Occupations requiring physical activity had significantly higher frequency of UI than those without. Other environmental work conditions as unclean or uncomfortable workplaces had no significant relationship with UI. Menopause patients had 2.8 times higher risk to develop UI. The mean age, mean number of parities, vaginal delivery, median duration of cough, cough severity index, and cough visual analogue scale were significantly higher in UI patients. The logistic regression was performed to test effects of different risk factors on UI. Results indicated that age, type of occupations according to physical activity, and cough severity index were independently statistically significant risk factors for UI in female patients with chronic cough. Conclusion UI is common in female patients with chronic cough (55%). Age, type of occupations according to physical activity, and cough severity index were independently significant risk factors for UI in female patients with chronic cough.